Baseline prognostic predictors in classical Hodgkin Lymphoma: a retrospective, single-center analysis on patients treated with PET/CT-guided ABVD - Cellini, Alessandro; Cavarretta, Chiara Adele; Angotzi, Francesco; Ruocco, Valeria; Serafin, Andrea; Danesin, Nicolò; Pizzi, Marco; Gregianin, Michele; Vio, Stefania; Crimì, Filippo; Vianello, Federica; Piazza, Francesco; et al. (Frontiers in Oncology, 2024)
IntroductionThe identification of baseline prognostic factors in Classical Hodgkin Lymphoma could help in tailoring a risk-based approach as the therapeutic landscape expands. Currently, the International Prognostic Score (IPS) represents the most used prediction tool in clinical practice, but other potential baseline risk predictors have been identified.MethodsWe performed a retrospective analysis in a cohort of 274 patients treated with 18FDG-PET/CT-guided ABVD to assess the prognostic significance of the IPS risk factors, and to validate the impact of the peripheral blood lymphocyte to monocyte (LMR) and neutrophil to lymphocyte (NLR) ratios on prognosis definition.ResultsAmong the considered risk factors, stage IV disease (HR 1.83), leukocytosis (HR 2.28), anemia (HR 3.23) and low LMR (HR 2.01) significantly predicted PFS, whereas male sex (HR 2.93), stage IV disease (HR 3.00) and lymphopenia (HR 7.84) significantly predicted OS. A 4 variable and a 3 variable prognostic system was subsequently proposed for PFS and OS, respectively. In both cases, a stark decrease in the survival probability was documented as the score increased. Moreover, by selecting only the significant IPS items and considering a more recently proposed prognostic factor (LMR) we were able to better identify patients at higher risk of relapsing after PET/CT-guided ABVD.DiscussionAlthough the IPS was still able to identify a subgroup of high-risk patients within our cohort of individuals treated with PET/CT-guided ABVD, not all the risk factors that it considers were found to have an impact on survival times. Moreover, by selecting only the significant IPS items and considering a more recently proposed prognostic factor (LMR) we were able to better identify patients at higher risk of relapse, in an effort to contribute to the building of a modern risk prediction tool that can help guide treatment choices.